A Synthesis and Characterization of Gold Nanoparticles Using The Bioreductor Bay Leaf (Syzygium polyanthum) (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2020)
Bay leaf extract has been used successfully in the synthesis of gold nanoparticles. This is indicated by the color change from the gold solution which is yellow to burgundy after the addition of the bay leaf extract and the resulting wavelength is in the range of 500 - 550 nm which indicates that gold nanoparticles have been formed. The growth and stability of the resulting gold nanoparticles were observed using UV-Vis Spectroscopy. Particle Size Analyzer (PSA), Scanning Electron Microscope (SEM), X-Ray Spectrometer Diffractometer (XRD) and Fourir Transform InfraRed (FTIR) were used to characterize Nanoparticles are produced before they are made into blood sugar nanosensors. The maximum wavelength was obtained at a wave of 533 nm using a UV-Vis spectrophotometer. The particle size was determined using PSA with average particle a size distribution of 15.49 nm.